Nanoimprint induced electrical type conversion in HgCdTe - Martyniuk, M.; Umana-Membreno, G.; Sewell, R.; Westerhout, R.; Musca, C.; Dell, J.; Antoszewski, J.; Faraone, L.; Macintyre, D.; Thoms, S.; Ironside, Charlie (2010)
We report supporting evidence that is consistent with p- to n-type conversion of HgCdTe that is induced by surface indentation, as the progress towards the fabrication of photovoltaic infrared detectors by direct imprinting. © 2010 IEEE.